Software paradigms - Kaisler, Stephen H. (Stephen Hendrick) (Hoboken, N.J. : Wiley-Interscience, 2005)
Software Paradigms provides the first complete compilation of software paradigms commonly used to develop large software applications, with coverage ranging from discrete problems to full-scale applications. The book focuses on providing a structure for understanding a hierarchy of software development approaches, and showing the relationships between the different models.
SOFTWARE PARADIGMS; CONTENTS; ADVICE FOR THE INSTRUCTOR; ACKNOWLEDGMENTS; 1 Introduction; 2 Paradigm Overview; I DESIGN PATTERNS; II COMPONENTS; III SOFTWARE ARCHITECTURES; IV FRAMEWORKS; BIBLIOGRAPHY; GLOSSARY; INDEX.
Includes bibliographical references (pages 413-426) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Computer software -- Development; REFERENCE -- General; Computer software -- Development; Programmatuurtechniek; Paradigma's.